Thermal design for a communications satellite payload module - Murat, Yunus; Mercan, Hatice; Sozbir, Nedim; Dalkilic, Ahmet Selim (SAGE PUBLICATIONS LTD, 2025)
Satellite design and manufacturing studies have become crucial due to their exposure to extreme thermal conditions in outer space. Thermal management systems are necessary to maintain acceptable temperatures for equipment on satellites' structural panels. Accurate modeling, simulation, and testing are necessary to handle high-gradient temperature cycles, considering worst-case scenarios. The study aimed to design, model, and simulate a geostationary communication satellite using finite element method-based software, analyzing thermal modeling, and extraterrestrial satellites. The literature on controlling satellite temperature is limited, with most studies on cube and nano satellites. No scholarly work combines geosynchronous satellite thermal modeling with finite element analysis, which is crucial for understanding satellite thermal dynamics and solving structural and thermal problems in satellite design. A heat pipe network and MLI are placed on the panel, ensuring a homogeneous temperature distribution. In the worst-case scenario, a 2.8 m2 radiator area is used to eliminate heat dissipation from equipment. Analytical investigation is conducted to assess heat rejection capabilities of payload panels, followed by creation and implementation of reduced thermal mathematical models using commercial software. The worst hot-case analysis shows all equipment remains below upper-temperature limits, with heat pipes preventing excessive hot areas. The worst cold-case analysis requires a heater power of 480 W, with a 50% duty ratio aiming for 960 W. The FEM analysis reveals a duty ratio of 55% for panel heaters. Finally, the thermal design of the satellite can be used to maintain the equipment within its temperature limits.
Keywords: Satellite thermal design; thermal modeling; orbit simulation; finite element method; satellite project phases; Engineering